Discus (Canaridiscus) rupivagus sp. nov., a rock-dwelling species from La Gomera, Canary Islands (Gastropoda: Pulmonata: Discidae) - Rähle, Wolfgang; Allgaier, Christoph (Zootaxa, 2011)
Yanes et al. (2011) assume that the endemic Discidae from the Madeiran and Canarian Islands are members of the single genus Atlantica Ancey, with Atlantica s.str. and Canaridiscus Alonso & Ibañez as subgenera. As long as the anatomy of the type-species of Atlantica [Discus guerinianus (R.T. Lowe) from Madeira] is not known however, we do not follow this designation but maintain the genus Discus with the subgenera Atlantica and Canaridiscus. The subgenus Canaridiscus has been established by Alonso & Ibañez (in Yanes et al. 2011) for two newly discovered Canarian species, anagaensis Ibañez & D. Holyoak from the northeastern Anaga mountains (Tenerife), and saproxylophagus Alonso, G. Holyoak & Yanes from the National Park of Garajonay (La Gomera). The most remarkable feature of the new taxon is the genital system with a long or very long penis, unknown in other Discidae. Here we deal with the occurence of an additional Canaridiscus species, living near Casas de Encherada in the eastern part of La Gomera, where it has been found hidden in narrow rock crevices.